mdm-miR828 Participates in the Feedback Loop to Regulate Anthocyanin Accumulation in Apple Peel - Zhang, Bo; Yang, Hui-Juan; Yang, Ya-Zhou; Zhu, Zhen-Zhen; Li, Ya-Nan; Qu, Dong; Zhao, Zheng-Yang (Frontiers in Plant Science, 2020)
Anthocyanins are responsible for the red pigmentation in the peel of apple (Malus × domestica Borkh.) fruit. Relatively few studies have investigated anthocyanins at the posttranscriptional level. MicroRNAs play an important role in plant growth and development by regulating gene expression at the posttranscriptional level. In this study, mdm-miR828 showed a relatively low expression level during the rapid fruit coloration period. However, the mdm-miR828 expression level increased in the late fruit coloration stage. Overexpression of mdm-miR828 inhibited anthocyanin synthesis in apple and Arabidopsis. Dual-luciferase and yeast one-hybrid assays showed that MdMYB1 is capable of binding to the promoter of mdm-MIR828b to promote its expression. The results indicate that mdm-miR828 is involved in a feedback regulatory mechanism associated with anthocyanin accumulation in apple. In addition, mdm-miR828 is involved in the inhibition of anthocyanin accumulation in response to high temperature.